Eco solution increases fish rehabilitation. Issue 2 (February 2017) - Smith, Clint; Spooner, Ryan; Valve, Singer
Abstract : The Bull Run Watershed is the primary drinking water supply for the City of Portland in the US. It also plays an important role in supporting the larger aquatic ecosystem of the Sandy and Lower Columbia rivers where, due to warm summer water temperatures, some of the fish species have recently been in significant decline.